2005
DOI: 10.1111/j.1365-2486.2005.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Grassland yield declined by a quarter in 5 years of free‐air ozone fumigation

Abstract: The sensitivity of seminatural grasslands to ozone (O 3 ) pollution is not well known, in spite of the important function of these common ecosystems for agriculture and nature conservation. A 5-year field experiment was carried out at a rural, mid-elevation site at Le Mouret (Switzerland) to investigate the effect of elevated O 3 on yield and species composition of a permanent, extensively managed, species-rich old pasture. Using a free-air fumigation system, circular plots of 7 m diameter were exposed to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 42 publications
(57 reference statements)
0
50
0
2
Order By: Relevance
“…Thus, the response to O3 observed in an annual community was in the range of the effects reported for individual species. By contrast, well established perennial grassland communities have shown higher resilience to O3 effects when comparing to individual component species (Volk et al, 2006;Stampfli and Fuhrer, 2010). On the other hand, our experimental annual community seemed to be more sensitive to O3 that perennial grasslands since significant effects were detected after few weeks of O3 exposure.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, the response to O3 observed in an annual community was in the range of the effects reported for individual species. By contrast, well established perennial grassland communities have shown higher resilience to O3 effects when comparing to individual component species (Volk et al, 2006;Stampfli and Fuhrer, 2010). On the other hand, our experimental annual community seemed to be more sensitive to O3 that perennial grasslands since significant effects were detected after few weeks of O3 exposure.…”
Section: Discussionmentioning
confidence: 63%
“…These authors found that the ozone levels in each region were most sensitive to domestic emissions, but transport of ozone and its precursors from foreign regions was also important. The importance of foreign emissions on domestic ozone levels therefore requires a good understanding of the terrestrial BVOC and NO x emission patterns (e.g., Chameides et al, 1988;Pierce et al, 1998;Wang and Shallcross, 2000;Sanderson et al, 2003a;Barket Jr. et al, 2004;von Kuhlmann et al, 2004;Folberth et al, 2006;Wu et al, 2007). Wu et al (2009) showed that the response of ozone levels to changes in emissions of NO x are non-linear outside of the summer months, but are linear during summer, when ozone production is limited by NO x levels.…”
Section: Processes In the Tropospherementioning
confidence: 99%
“…Free Air CO 2 Enrichment (FACE) and related experiments using ozone-enriched air indicate a nonlinear interaction between plant responses to CO 2 and O 3 . Models of plant-O 3 interactions must be able to replicate results obtained in the enrichment experiments, e.g., for aspen trees (Karnosky, 2003;Karnosky et al, 2005) or at a Swiss grassland site (Volk et al, 2006) where plots are exposed for multiple years to combinations of ambient and elevated concentrations of CO 2 and O 3 .…”
Section: Ozone Effects On Vegetationmentioning
confidence: 99%
“…5 kg ha −1 yr −1 ) at high altitude and in inner-alpine valleys (Rihm and Kurz, 2001) like our study site. Tropospheric O 3 concentrations have reached levels that affect plant growth (Fuhrer et al, 1997;Ashmore, 2005;Volk et al, 2006), and the least conservative estimates predict mean annual O 3 background concentrations to rise to 84 ppb by 2100 (Vingarzan, 2004;Derwent et al, 2007). Ozone concentrations are particularly high at high-altitude sites, due to reduced nocturnal degradation and deposition, and the natural gradient under free-tropospheric conditions (Chevalier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%